2003
DOI: 10.1097/00001756-200303240-00019
|View full text |Cite
|
Sign up to set email alerts
|

Retrosplenial cortical activation in the fibromyalgia syndrome

Abstract: To study the CNS in chronic muscular pain typical of fibromyalgia we compared PET measures of regional cerebral blood flow (rCBF) in eight fibromyalgic patients and controls at rest. Higher rCBF for patients than controls was found bilaterally in the retrosplenial cortex. Lower rCBF for patients than controls were seen in the left frontal, temporal, parietal, and occipital cortices. The higher retroplenial rCBF in patients than controls may reflect increased attention towards sub-noxious somatosensory signalin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
26
0
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(32 citation statements)
references
References 18 publications
5
26
0
1
Order By: Relevance
“…Interestingly, this altered fronto-hippocampal connectivity and impaired memory was not associated with a significant change in overall firing rate, just a change in firing rhythm. Similarly, we found no overall increases in CBF, an index of neural activity, in pain-related brain regions, which is consistent with many previous investigations (Hsieh et al, 1995;Wik et al, 2003;Yunus et al, 2004). These data suggest that altered thalamocortical rhythm, and not necessarily increased overall activity in somatosensory processing regions, can result in the persistent perception of pain.…”
supporting
confidence: 93%
“…Interestingly, this altered fronto-hippocampal connectivity and impaired memory was not associated with a significant change in overall firing rate, just a change in firing rhythm. Similarly, we found no overall increases in CBF, an index of neural activity, in pain-related brain regions, which is consistent with many previous investigations (Hsieh et al, 1995;Wik et al, 2003;Yunus et al, 2004). These data suggest that altered thalamocortical rhythm, and not necessarily increased overall activity in somatosensory processing regions, can result in the persistent perception of pain.…”
supporting
confidence: 93%
“…Single-photon-emission-computed tomography (SPECT) imaging has demonstrated regional cerebral blood flow (rCBF) decrease in thalamus and pontine region in patients of FM [13, 14]. The ensuing PET study has not only shown rCBF decrease in several brain regions, supporting the dysfunctional cognitive processing of pain, but also higher retrosplenial rCBF, suggesting secondary hyperalgesia [15]. Since the inception of functional magnetic resonance imaging (fMRI), it became easier to infer neural activity by proxy of blood-oxygen-level-dependent (BOLD) contrast without the need of radioactive tracer or contrast agent.…”
Section: Introductionmentioning
confidence: 99%
“…Studies comparing rCBF at rest in chronic pain patients to normal controls [11,18,21,25,26,41] have reported reductions or asymmetric changes in thalamus and reductions in frontal, temporal, parietal, occipital regions. These reports are not conclusive since knowledge about cerebral pain mechanisms is mainly based on experimental studies.…”
mentioning
confidence: 99%